Potential of Tunisian Alfa (Stipa tenassicima) fibers for energy recovery to 2G bioethanol: Study of pretreatment, enzymatic saccharification and fermentation. (November 2016) - Zaafouri, Kaouther; Ziadi, Manel; Ben Farah, Rim; Farid, Mokhtar; Hamdi, Moktar; Regaya, Imed
Abstract: The aim of this study is to optimize the pretreatment of Alfa fibers Stipa tenacissima for the production of bioethanol second generation. The Alfa is a complex lignocellulosic substrate. It is mainly composed by cellulose (49.09% ± 0.015), hemicellulose (18.20% ± 0.3) and lignins (16.25% ± 0.475). In the current study, process of production of the biofuel was carried out through three successive steps: a pretreatment performed with dilute acid (3%) at 120 °C during 30 min, an enzymatic saccharification by a commercial enzyme (AP2) and fermentation steps. Dilute acid pretreatment of the biomass resulted in an efficient degradation of cellulose and hemicellulose by increasing the total sugars (39.951 g/L) and reducing sugars (22.36 g/L) yields. These yields were increased after enzymatic saccharification to reach 22.7 g/L of reducing sugars. The fermentation of the aforementioned hydrolysate was efficient with ethanol production being 36.36% of theoretical maximum. Highlights: Alfa Stipa tenassicima is a promising lignocellulosic substrate for 2G-bioethanol production in Tunisia. Alfa fibers pretreatment performed with H2 SO4 (3%) at 120 °C for 30 minutes gives a reducing sugars efficiency of 41.27%. A yield of 88.10% of reducing sugars; was converted to alcohol; which correspond to 36.36% of ethanol from cellulose. The potential conversion yield of ethanol is 10 kg of Alfa fibers to 1 liter of bioethanol second generation.